EFFECT OF SCARIFICATION METHOD ON THE GERMINATION AND SEEDLING GROWTH OF FLAMBOYANT: DELONIX REGIA - Mohammad, M.; Abdulrahman, A. (FUDMA JOURNAL OF SCIENCES, 2023)
Effect of scarification method on the germination and seedling growth of flamboyant (Delonixregia) was investigated. The experiment was conducted at botanical garden Federal University Dutse, Jigawa State (Latitude 11.000N to 13.00N0 and longitude 8.000E to 10.50E). Flamboyant (Delonixregia) seed were collected from Kundila garden in Kano State. The experimental design used was completely randomized block design. There were 15 replications per treatment. The experiment consists of three treatments; acid treatment by soaking the seed in 75% H2s04 for 2hours, mechanical treatment of the hard seed coat using sand paper and treatment of the seed with hot water for 10minute. Data was collected on seedling emergence, seedling height and germination rate and analyzed using analysis of variance at 5% significance level. There were significance differences between the treatments. The highest germination rate of 100% was observed in mechanically scarified seeds while the control recorded the lowest germination rate of 20%.In seedling emergence, the highest emergence 66.6% was induced by hot water treatment and the least were the untreated seed which recorded 20%. In seedling height the highest result was obtained with mechanical treatment and the least were the control plants. Mechanical scarification significantly inducedhigh and quick germination more than any of the treatments. Therefore selection of Mechanical Scarification method would be a wiser choice as it is more effective in breaking the Seed Dormancy of Delonixregia.Results of this research may serve as useful information in the production and improvement of Delonixregia species, as knowledge on seed germination requirements is a critical